A questão do uso da próclise em início de frase na obra Esthesia Philologia, de Augusto Meira (1909) - VILHENA, Cleonice Rodrigues de (2019)
This work has as general objective to analyze the phenomenon of pronominal placement in the work Esthesia Philologica: Variações Pronominaes, by Augusto Meira, published in 1909. For this, a study is made on the life of José Augusto Meira Dantas; understand the historical and linguistic context in which the work was written and analyze the phenomena of pronominal placement in the light of Augusto Meira. We used as a theoretical-methodological orientation the discussions about the pronominal placement of Meira (1909), Almeida (1969), and the contemporary author Bagno (2012, 2017). We can understand that the work of Augusto Meira, despite being from the beginning of the twentieth century, still today causes impasse among grammarians regarding the placement of unstressed oblique pronouns at the beginning of sentence, which makes us reflect how still we are stuck with concepts mistakes that do not allow us to have our own identity, which does not allow us to evolve, in a way, to a truly Brazilian language.